Ketahanan Beton Normal Terhadap Air Gambut Di Kota Palangka Raya - Noviyanthy Handayani (Media Ilmiah Teknik Sipil, 2018)
The city of Palangka Raya has these peatlands spread across several regions including populated areas. This needs special attention in the world of concrete construction because the peatland has peat water with a high level of organic matter, low acidity (pH) which results in acidic water. The acidity of peat water will cause problems in concrete construction because it will affect the physical and mechanical properties of concrete which will make the concrete corrosive. This research method is by making 27 K-250 concrete samples, each of which three examples will be immersed in peat water, Kahayan river water, and tap water for one month, two months and three months. The results showed that the concrete soaked in peat water had the most significant decline compared to the concrete soaked in Kahayan river water and tap water, which was 8.798% of the planned concrete compressive strength of 250 kg / cm2 while the concrete with river water immersion decreased by 5.882% and tap water immersion 2.966% from the planned concrete compressive strength of 250 kg / cm2.